ОПИСАНИЕ СИНОНИМИИ В ЛЕКСИКО-СЕМАНТИЧЕСКОЙ СИСТЕМЕ ЯЗЫКА - Каллибекова, Г.А. (SCIENCE and SOCIETY, 2024)
The description of synonyms involves clarifying their place in the lexical system of a language among other lexical units, revealing the semantic essence of synonyms, problems of identity and difference of synonyms, characterizing the functions of synonyms in language and speech.